Comparison of double-strand braided polyester sutures tension band (Nice knot) with cable tension band in transverse patellar fractures. Issue 10 (October 2021) - Yin, Zhaowei; Yan, Junwei; Ge, Dawei; Yang, Lei; Liang, Bin; Fei, Junliang
Highligts: Suture tension band technique (Nice knot) achieved similar strength and obtained equivalent clinical results compared with cable tension band. More convenient operations, less cost and fewer complications were found in suture fixation (Nice knot). Nice knot technique can be applied to all tension band techniques, including olecranon fractures, malleolus fractures, etc. Abstract: Background: The tension band technique is the most common method for internal fixation of transverse patellar fractures. Titanium cable and high-strength sutures have been successfully applied in this treatment; however, few studies have compared the Nice knot technique using sutures with the standard cable technique. Whether the suture technique (Nice knot) provides preferable results compared with those of the cable technique is unclear. Methods: Forty patients with transverse patellar fractures participated in this study. Twenty patients underwent sutures tension band fixation (Nice knot), and the others were managed with cable tension bands. All patients were followed up at 1, 3, 6, and 12 months. Pain was measured by VAS scores, flexion and extension of the knee were measured in degrees by goniometry, and knee function was evaluated using the Böstman clinical grading scale. Results: The two groups had equal distributions in age, gender, injured side, and fracture classification. The mean operation time in the suture group was shorter (55.75±9.77 minutes versus 64.25±9.63 minutes). The VAS score was comparable in the two groups at the 1-month, 3-month, and 6-month follow-ups; however, the score was lower at 12 months postoperatively in the suture group (P=0.037). No significant difference was found in flexion, extension, Böstman score, or fracture healing time in either group (P>0.05). Postoperative complications were higher in the cable group (9 versus 2) (P = 0.031) but were mostly related to symptomatic soft tissue irritation. Conclusion: The suture tension band technique using braided polyester nonabsorbable sutures tied with Nice knot was as effective as the cable tension band technique for transverse patellar fracture management. However, more convenient operations, less cost and fewer complications were found in suture fixation (Nice knot).